Effects of plyometric and pull training on performance and selected strength characteristics of junior male weightlifter - İ. İnce; A. Şentürk (Physical Education of Students)
Purpose: The aim of this study was to investigate the effect of plyometric and pull training added an Olympic weightlifting training program (twice a week for 8 wk) on performance and selected strength characteristics in junior male weightlifter. Material: The participants [n = 34; age: 16.03 ± 0.9 y; mass: 74.78 ± 14.86 kg; height: 170.53 ± 6.81 cm] were randomized into a pull (n = 11), a plyometric (n = 12), and a control (n= 11) groups. The groups trained 6 days a week during the 8-week study period. The pull group performed four pull exercises and the plyometric group performed four plyometric exercises added to Olympic weightlifting program for 2 days a week, and the control group performed an Olympic weightlifting program alone. Analysis of variance and Magnitude-based inferences used to determine whether a significant difference existed among groups on snatch clean and jerk total (SCT), squat (SQ), back strength (BS), countermovement jump (CMJ), 30 sec. repeated jump height (RJH) and peak barbell velocity (PV). Results: The ANOVA showed a time × group interaction for SCT, BS and RJH. The MBI indicated positive changes for SCT in control group, for BS in pull group and for RJH in plyometric group. The results for the PV decrease in plyometric and pull group indicated no significant time × group interaction, but there was a significant main effects. ASK "Inserisci l'aim" \* MERGEFORMAT ASK \* MERGEFORMAT Conclusions: The results of this study showed that the addition of pull or plyometric training to an Olympic weightlifting program interfered with weightlifting performances.